Tommaso Landolfi’s «LA BIERE DU PECHEUR»:a publishing process (Prassi Ecdotiche della Modernità Letteraria, 2020)
This contribution retraces, through the examination of the letters to editor Enrico Vallecchi, the publishing process of Tommaso Landolfi’s La Biere du pecheur and its complex paratext. In his first diary, the author experiments an explicit autobiographical writing. At the same time, he refuses to appear in public, even in picture, or to provide any information about himself and gradually isolated from the world.